Navigating the Research Landscape: A Guide to the Selection of the Right Research Design - Sharma, Lok Raj; Jha, Sonelal; Koirala, Rabin; Aryal, Umesh; Bhattarai, Teknath (International Research Journal of MMC, 2023)
Research design, which is a plan or framework for conducting an investigatory study, engrosses the ways for collecting and analyzing data. It is circumspectly planned in advance as it influences the quality and validity of the research outcomes. There are broadly three sorts of research designs, namely quantitative, qualitative and mixed methods research designs. Quantitative research designs involve the collection and analysis of numerical data, qualitative research designs include the collection and analysis of non-numerical data, such as words, images, and observations, and mixed methods research designs embrace both qualitative and quantitative data. There are also certain types of research designs under these major research designs, and a researcher normally has to select one of them to carry out his/ her research study. The key objective of this article is to navigate the research landscape and provide a concise guide to the selection of the right research design. This article based on the secondary qualitative data employs books and journal articles as the sources of data. Based on an analysis of some prominent works in the field of research, this article offers an overview of research designs and discusses its main types. It will provide the researchers with a clear guideline to the selection of the right research design.It will assist research neophytes in particular and other researchers in general.